Globalisation and the Decoupling of Inflation from Domestic Labour Costs - Emanuel Kohlscheen; Richhild Moessner (Center for Economic Studies and ifo Institute (CESifo), 2021)
We provide novel systematic cross-country evidence that the link between domestic labour markets and CPI inflation has weakened considerably in advanced economies during recent decades. The central estimate is that the short-run pass-through from domestic labour cost changes to core CPI inflation decreased from 0.25 in the 1980s to just 0.02 in the 2010s, while the longrun pass-through fell from 0.36 to 0.03, with the estimates in the 2010s no longer significant. We show that the timing of the collapse in the pass-through coincides with a steep increase in import penetration from a group of major manufacturing EMEs around the turn of the millennium, which signals increased competition and market contestability.
Keywords: E31; E50; F10; F60; J30; 330; competition; globalisation; import penetration; inflation; labour market; pass-through; wage